Role of Mifepristone in treatment of uterine fibroid: an experience from tertiary care centre in South India - Nachiketha, S. V.; Hadi, Veena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Uterine fibroid are the most common benign tumour of the uterus and is seen in 20% of women in their reproductive age group. The aim of the study was to evaluate effect of Mifepristone on uterine fibroid with reference to reduction in size of fibroid and change in symptomatic profile. Methods: It is a hospital based interventional study conducted at KIMS Hubli hospital. 98 patients with symptomatic fibroid uterus were given 50mg of Mifepristone on alternate day for 3 months. Results: Mifepristone treatment significantly reduced mean PBAC score from baseline score of 212.61 to 20.39 at the end of 3rd month of therapy. Mean fibroid volume also reduced significantly from baseline value of 237.95cm3 to 30.45cm3 after 3 months of treatment. At the end of therapy hemoglobin was raised from 9.57g/dl at baseline to 10.42g/dl after 3 months of treatment. No major side effects were observed, and 7% patients had hysterectomy. Conclusions: Mifepristone is very useful option in perimenopausal women with symptomatic fibroid. It reduces fibroid size and its symptoms without any major side effects. However, future long term RCTs are needed to assess the safety and efficacy of Mifepristone.